Potential application of remote sensing in monitoring ecosystem services of forests, mangroves and urban areas. Issue 8 (3rd August 2017) - Avtar, Ram; Kumar, Pankaj; Oono, Akiko; Saraswat, Chitresh; Dorji, Singay; Hlaing, Zarchi
Abstract: The application of remote sensing (RS) techniques to monitor ecosystem services has increased in recent years. Nevertheless, the potential application of RS to monitor some of ecosystem services is still challenging. The paper reviews the applications of RS to monitor ecosystem services of forests, mangroves and urban areas. Satellite data provide substantial information about dynamics of environmental changes over time from local to global scale. These information are useful data sources for the people who are involved in the on-going evaluation and decision-making process to manage ecosystem. Many recent research papers on the topic were reviewed to find new applications and limitations of RS for monitoring ecosystem services. Advanced RS techniques have high potential to monitor ecosystem services with the advancement of sensors ranging from aerial photography to high and medium resolution optical RS and from hyperspectral RS to microwave RS.